A novel angiotensin-converting enzyme inhibitory peptide from rabbit meat protein hydrolysate: identification, molecular mechanism, and antihypertensive effect in vivo. Issue 23 (16th November 2021) - Chen, Junbo; Yu, Xiaodong; Huang, Wangxiang; Wang, Chen; He, Qiyi
Abstract : A novel ACE inhibitory peptide (WGAP) was purified from rabbit meat hydrolysates. WGAP acts as non-competitive inhibition kinetics and shows significant  in vivo  antihypertensive effects in rats.  Abstract : Bioactive peptides exhibiting angiotensin-converting enzyme (ACE) inhibitory effects and extracted from natural foods have potential as healthy and safe therapeutics for high blood pressure. The aim of this study was to isolate and purify ACE inhibitory peptides from rabbit meat protein hydrolysate, to explore the underlying mechanisms by molecular docking, and to evaluate the antihypertensive effects in vivo . A novel ACE inhibitory tetrapeptide Trp-Gly-Ala-Pro (WGAP) was identified and purified from a bromelain hydrolysate. WGAP acted against ACE in a non-competitive manner with an IC50 of 140.70 ± 4.51 μM. It was resistant to enzymatic degradation by pepsin and trypsin in vitro . Molecular docking analysis indicated that WGAP formed stable hydrogen bonds with ACE residues His353, Ala354 and ALA356. In vivo, 100 mg kg −1 WGAP significantly reduced systolic and diastolic blood pressure in hypertensive rats by up to 42.66 ± 2.87 and 28.56 ± 2.71 mmHg, respectively, 4 h after oral administration. ACE inhibitory peptides derived from rabbit meat have potential antihypertensive effects and provide a new route for the exploration of novel hypertension inhibitors and the utilization of rabbit meat.